TEACHING AND LEARNING ENGLISH FOR VISUALLY IMPAIRED STUDENTS: AN ETHNOGRAPHIC CASE STUDY - Susanto Susanto; Deri Sis Nanda (English Review: Journal of English Education, 2018)
In this article we report an ethnographic case study of observing the teaching and learning of English at a school for visually impaired students in Bandar Lampung, Indonesia. Data collection included student and teacher interviews. It also covered class observation and used a social constructivist framework of disability. The study revealed that the students received inadequate modifications of instruction in foreign language learning. However, the students used a variety of resources with the screen reader technology such as Non Visual Desktop Access (NVDA) and Job Access with Speech (JAWS). These findings suggest that visually impaired students actually can have unique ways of learning foreign language supported by the assistive technology. These abilities should be acknowledged to obtain the perspectives of students who receive disability specific education. Moreover, the study might provide a further facet to the research especially on the importance of learning strategies in special education.Keywords: visual impairment; language education; learning strategy; special education.